TAFSIR AYAT-AYAT GENDER ALA AMINA WADUD PERSPEKTIF HERMENEUTIKA GADAMER - Irsyadunnas, Irsyadunnas (Musawa Jurnal Studi Gender dan Islam, 2015)
In the interpretation of the verses of the Qurâ€™an, gender has undergone considerableÂ  and dynamic developments. The classical commentators tend to interpret verses textually â€“ normatively, while feminists tend to interpret the verses contextually â€“ sociologically. Along with the developments in the methods or approaches to the contemporary interpretation of the Qurâ€™an, one of the methods or approaches used by feminists is hermeneutics. Through this method or approach, Amina Wadud tries to interpret verses related to the creation of women, womenâ€™s leadership, and the problems of polygamy. The result is that the origin of human beings, both males and females, came from a single nafs which is part of the system pairs (nafs itself and its zawj). The leadership clause should be understood in the context of society as a whole through the concept of â€œfunctionalistâ€. On polygamy, there is no direct evidence from the Koran about the permissibility of polygamous marriage, especially in regard to the three validations often cited by proponents, namely financial reasons, reasons of infertility, and the reason the fulfillment of lust or sexual needs.